III International Scientific and Practical Conference “Eagles of the Palearctic: Study and Conservation”, September 24–29, 2023, Almaty Resort Sanatorium, Almaty, Kazakhstan - Igor V. Karyakin; Elvira G. Nikolenko (Пернатые хищники и их охрана)
All Eurasian species of eagles are more or less rare, so saving them requires the combined efforts of countries where the birds breed, migrate and winter. Planning protective actions requires studying the status of the bird populations, as well as negative factors affecting them.